MODULATORY EFFECT OF PTEROSTILBENE ON TAIL TENDON COLLAGEN IN TYPE 2 DIABETIC RATS - Pidaran Murugan1*, Sivaprakasam Maneemegalai2 (Chelonian Research Foundation, 2024)
Introduction: The research was determined to investigate on the effects of pterostilbene and tetrahydrocurcumin (THC) on the collagen content and its physical and chemical characteristics in the tail tendon of streptozotocin (STZ) induced diabetic rats. Purpose: Ptrerostilbene and THC has been tested clinically and found to be effective in non-insulin dependent diabetes mellitus patients. Experimental design: In the experiment, a total of 24 rats (18 diabetic surviving rats, 6 normal rats) were used. The rats were divided into four groups of six each, after the induction of STZ diabetes. The experimental period was 45 days. Group 1: Normal rats. Group 2: Diabetic control rats. Group 3: Diabetic rats treated with THC (80 mg/kg body weight) in aqueous suspension daily using an intragastric tube for 45 days. Group 4: Diabetic rats treated with pterostilbene (40 mg/kg body weight) in aqueous suspension daily using an intragastric tube for 45 days Results: In the case of diabetic rats treated with pterostilbene and THC, the collagen content was significantly decreased. The extent of glycation, cross-linking and collagen linked fluorescence were significantly reduced. In addition to that, the collagen content in the  region as well as in the high molecular weight region in tail tendon was near normal when compared to diabetic control groups. The reduction in the advanced glycation and cross-linking of collagen in pterostilbene and THC treated rats to their antiperoxidative activity directly influence the collagen cross-linking and advanced glycation end products formation. Conclusion: The administration of pterosilbene and THC had a positive influence on the content of collagen and its properties in streptozotocin and nicotinamide diabetic rats. The pterosilbene administration was found to be more effective than THC. Keywords: tetrahydrocurcumin, pterostilbene, collagen, streptozotocin, nicotinamide, blood glucose, plasma insulin